Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Pada Mata Pelajaran Matematika Siswa Kelas IV SD Negeri Tingkir Tengah 01 - Eralisa, Fitriana Nely (Caruban: Jurnal Ilmiah Ilmu Pendidikan Dasar, 2024)
This research is based on the low critical thinking skills of students. The aim of this research is to improve students' critical thinking skills through the Discovery Learning learning model in mathematics learning for fourth grade students at SD Negeri Tingkir Tengah 01. The application of the Discovery Learning model has six learning steps, namely Stimulation (stimulation or providing stimulation), Problem statement (statement or problem identification), Data collection (data collection), Data processing (data processing), Verification (proof), and Generalization (drawing conclusions or generalizations). The research method used in this research is Classroom Action Research (PTK). This PTK is carried out in 2 learning cycles in semester 2 of the 2023/2024 academic year. This research was carried out using a Stringer design which consists of three stages, namely look, think, and act. The subjects of this research were 27 grade IV students at SD Negeri Tingkir Tengah 01. Obtaining data using a self-assessment questionnaire instrument for critical thinking skills. Based on research, the results show that the average critical thinking skills of pre-cycle students is 62 with the highest score being 73 and the lowest score being 45 in the low category. In cycle I, the average data on students' critical thinking skills was 68 with the highest score being 78 while the lowest score was 42 in the medium category. Then in Cycle II, the average result of students' critical thinking skills increased to 79 with the highest score being 85 and the lowest score being 58 in the high category. Thus, it can be concluded that through the application of the Discovery Learning learning model it can improve critical thinking skills in mathematics subjects for fourth grade students at SD Negeri Tingkir Tengah 01.